2010
DOI: 10.1002/cncr.24914
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine versus bacille Calmette‐Guérin after initial bacille Calmette‐Guérin failure in non‐muscle‐invasive bladder cancer

Abstract: BACKGROUND:The efficacy of intravesical gemcitabine was evaluated compared with repeated administration of bacille Calmette-Guérin (BCG) after BCG failure in high-risk, non-muscle-invasive bladder cancer (BC). METHODS: In this multicenter, prospective, randomized, phase 2 trial, eligible patients were those with high-risk non-muscle-invasive BC, failing 1 course of BCG therapy. All patients were randomly allocated to Group A, receiving intravesical gemcitabine (at a dose of 2000 mg/50 mL) twice weekly for 6 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 29 publications
2
113
1
8
Order By: Relevance
“…This is lower than in the recent Phase II clinical trial comparing salvage intravesical gemcitabine (33% progression) vs. additional induction BCG (37.5% progression) in patients with recurrent NMIBC despite BCG at 2 years follow-up [11]. The rate of cystectomy was 62% at 5 years which is higher than previously published clinical trials which range from 33% to 56% at a follow-up of 1.5 to 3 years [11][12][13][14][15].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This is lower than in the recent Phase II clinical trial comparing salvage intravesical gemcitabine (33% progression) vs. additional induction BCG (37.5% progression) in patients with recurrent NMIBC despite BCG at 2 years follow-up [11]. The rate of cystectomy was 62% at 5 years which is higher than previously published clinical trials which range from 33% to 56% at a follow-up of 1.5 to 3 years [11][12][13][14][15].…”
Section: Discussioncontrasting
confidence: 55%
“…The study population of 1300 virtual patients is significantly higher than most published series on BCG refractory patients which range from 20-100 patients [11][12][13][14][15]. Our virtual series contained 58% of patients with clinical stage T1 urothelial carcinoma prior to randomization which falls within the range of previous BCG failure trials where 47%-78% had cT1 tumors [11,15]. Thirty-seven percent of patients had cTis prior to the start of the virtual trial which falls within the range of 31%-77% from prior studies [11,15].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Overall recurrence was 25% for gemcitabine-treated patients versus 30% for BCG-treated patients, and progression was equivalent between the groups. Di Lorenzo et al 32 showed that in carcinoma in situ (CIS) patients with BCG failure, gemcitabine treatment resulted in a recurrence rate of 52.5% (v. 87.5% for BCG-treated patients) and a 2-year recurrence-free survival rate of 19% (v. 3% for BCG). There was no improvement in the mean time to first recurrence or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Di Lorenzo et al [19] reported a better 2-year recurrence-free survival (3% vs. 19%, p<0.008) with BCG compared to GEM in cases with BCG failure. However this trend was not verified for disease-progression (37.5% vs. 33%, p=0.12) and both groups had similar rates of patients undergoing RC.…”
Section: Gemcitabinementioning
confidence: 96%